2003
DOI: 10.2202/1949-6605.1222
|View full text |Cite
|
Sign up to set email alerts
|

The Social Construction of Prejudice among Black and White College Students

Abstract: ❖ The purpose of this study was to determine if there is a distinctive difference between the prejudice of Black and White college students at a predominantly White Midwest university. Using focus groups, we explored the perceptions that Black and White undergraduate students have of each other and how they socially encounter each other on campus. We offer recommendations for practice based on the results of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…And Other Conversations About Race . In addition, Duhon (2002) describes how black elementary and secondary public school students are often “tracked” into highly segregated classes. Although their study focuses on a predominantly white university in the Midwest, Radloff and Evans (2003) findings concerning continued social distancing between blacks and whites is apparent on college campuses across the nation. Klagge (2003), a professor at Virginia Tech University, concludes that “few multiracial churches are successful” (p. 6), and therewith echoes Martin Luther King’s oft‐quoted statement that “the most segregated hour of Christian America is eleven o’clock on Sunday morning.”…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…And Other Conversations About Race . In addition, Duhon (2002) describes how black elementary and secondary public school students are often “tracked” into highly segregated classes. Although their study focuses on a predominantly white university in the Midwest, Radloff and Evans (2003) findings concerning continued social distancing between blacks and whites is apparent on college campuses across the nation. Klagge (2003), a professor at Virginia Tech University, concludes that “few multiracial churches are successful” (p. 6), and therewith echoes Martin Luther King’s oft‐quoted statement that “the most segregated hour of Christian America is eleven o’clock on Sunday morning.”…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Although their study focuses on a predominantly white university in the Midwest, Radloff and Evans (2003) findings concerning continued social distancing between blacks and whites is apparent on college campuses across the nation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…One view is that unconscious prejudices are widespread although many people deny that prejudices are operating today, and believe that the concerns over racism and stereotyping impacting society are unfounded (White, 1999). In one study of African American and Caucasian college students' perceptions of racism, one third of the white college students in the study did not believe that racism was a problem on their campuses while all of the black students believed that it was a problem (Radloff & Evans, 2003 (Cabrera, Nora, Terenzini, Pascarella, & Hagedorn, 1999). Students also believed that prejudice on campus was responsible for instructors' lower expectations of achievement for black students (Radloff & Evans, 20003).…”
Section: Stereotypes and Their Impactsmentioning
confidence: 99%
“…Harper and Hurtado's (2007) review focused on the racial climate studies conducted after Hurtado's 1992 report. In their summary of twenty-six climate studies, they reported that students' perceptions of the racial diversity climate varied by race, students of color often perceived their campus environments as racist, and reported incidents of prejudicial treatment (Ancis, Sedlacek, & Mohr, 2000;Cabrera & Nora, 1994;Cabrera et al, 1999;D'Augelli & Hershberger, 1993;Eimers & Pike, 1997;Helm, Sedlacek, & Prieto, 1998;Radloff & Evans, 2003;Rankin & Reason, 2005). They reported that climates focusing on the behavioral element of the campus diversity climate, particularly fostering cross-racial engagement, resulted in benefits for all students.…”
Section: Research On Racial Diversity Climatementioning
confidence: 99%